Physics, inconsistency, and quasi-truth - da Costa, Newton C. A.; Krause, Décio (Synthese (Dordrecht), 2014)
In this work, the first of a series, we study the nature of informal inconsistency in physics, focusing mainly on the foundations of quantum theory, and appealing to the concept of quasi-truth. We defend a pluralistic view of the philosophy of science, grounded on the existence of inconsistencies and on quasi-truth. Here, we treat only the 'classical aspects' of the subject, leaving for a forthcoming paper the 'non-classical' part.